Pengaruh Komunikasi Efektif Terhadap Kualitas Pelayanan Publik Terpadu Satu Pintu Di Dinas Kesehatan Kota Sukabumi - Muhammad Tanziil Suherman (STISIP Widyapuri Mandiri Sukabumi, 2023)
The main problem in this research lies in the quality of service, which according to the researcher's initial observations is caused by the ineffectiveness of the communication and information system. Based on the above reflections and considerations, the researcher intends to examine further in the form of dissertation research with the title